Effectiveness of Implementing the Independent Learning Curriculum in Chemistry Learning Processes at High Schools in Makassar City - Khaerunnisa, Khaerunnisa; Anwar, Muhammad; Majid, Ahmad Fudhail (Universitas Negeri Gorontalo, 2024)
This research aims to understand how the implementation of the independent learning curriculum is applied in the chemistry learning process and to determine the effectiveness of this curriculum's application in the chemistry learning process. The sample for this research is Class X.1 which consists of 30 students and 4 chemistry teachers who are the subjects of this research. Data collection was carried out by distributing questionnaires to chemistry teachers to understand how the independent learning curriculum is applied in the chemistry learning process and by administering a posttest to students to determine the effectiveness of the curriculum's application in the chemistry learning process. This research uses descriptive statistical analysis. The results of the descriptive statistical analysis of the questionnaire on the application of the independent learning curriculum obtained an average score of 81.75 with very good criteria, and the results of the descriptive statistical analysis of student learning outcomes obtained an average score of 78.1 with satisfactory criteria. Based on these analysis results, it can be concluded that the implementation of the independent learning curriculum in the chemistry learning process in class X.1 at SMAN 9 Makassar has been very well applied and the effectiveness of the independent learning curriculum in the learning process in class X.1 at SMAN 9 Makassar has been effective.